The Interdependence of Indonesia Coffee Futures and Spot Market and Its Relationship with Offshore Futures Market - Wulandari, Anis Erma; Harianto, Harianto; Arifin, Bustanul (Jurnal Manajemen dan Agribisnis, 2019)
In the Indonesia coffee premature market, it is important to confirm whether the futures market has interdependence with the spot market. Moreover, as the world’s largest coffee producers after Brazil, Vietnam, and Colombia, it is also important to examine the interdependence between Indonesia markets with the offshore futures market whose prices are used uses for local price determination. This study examined the granger causality relationship between Indonesia’s futures and spot market, and granger relationship between Indonesia and the offshore futures market using data of daily Arabica and Robusta coffee prices starting from January 2014 to June 2018. The test indicated that the futures market has a stronger ability to predict the spot market; therefore, price discovery in the futures market. Bidirectional causality relationship between Arabica offshore futures and spot market indicates market demand on Arabica coffee. In general, it’s identified unidirectional granger causality relationship between local and offshore futures market with information flows from the local futures market reflects the offshore market high expectation toward crop information during harvesting period both Arabica and Robusta. This is due to the importance of Indonesia’s coffee crop report to world aggregate coffee production.